Examining the Risk of Clot Formation in Diabetes Through Computational Analysis: An Approach Using Mathematical Modeling - Singh, Anuradha; P., Ashik Babu; Arora, Kavita; Shah, Sapna Ratan (International Journal of Applied Sciences and Biotechnology, 2024)
Our study delves into the heightened risk of blood clot formation in individuals with diabetes, a condition known for its potential to increase clotting tendencies, leading to severe complications like heart attacks and strokes. Utilizing a multidisciplinary approach, we integrate physiological data, principles of hemodynamic, and mathematical models to simulate the intricate dynamics of blood flow and clot formation within the vasculature of diabetic individuals. By considering critical factors such as altered blood viscosity, resistance to flow, endothelial dysfunction, and platelet aggregation, we gain valuable insights into the complex interactions between diabetes-related factors and the propensity for clotting. Factors like elevated levels of fibrinogen and other clotting factors contribute to blood thickening, increased resistance to flow, and heightened viscosity, exacerbating the clotting risk. As clots grow within blood vessels, they impede blood flow, elevating resistance and making blood movement more challenging. Moreover, the size of clots influences local blood viscosity, further complicating circulation. Through computational simulations, we explore diverse scenarios to evaluate how different parameters affect the risk of clot formation, providing crucial insights for developing preventive measures and targeted interventions tailored to diabetic patients' needs. Int. J. Appl. Sci. Biotechnol. Vol 12(2): 92-99.